(untitled) (Journal of the Sociology and Theory of Religion, 2019)
Feminist studies have unleashed wide public discussion of citizenship and gender equality, alongside the growth of social movements within religious activism opposed to feminist theories. This article analyzes the scientific production on the tension between religion and feminist studies, through an exploratory study of literature review of articles published in Portuguese scientific journals indexed to Scielo. From the content analysis of these studies the results point to the prevalence of articles related to monotheistic (Christian) religions, which mostly illustrate an androcentric view of religious discourse.